2020
DOI: 10.3390/foods9111530
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Olfactory–Oral Cross-Modal Interactions through Sensory and Chemical Characteristics of Italian Red Wines

Abstract: This work aimed at investigating red wine olfactory–oral cross-modal interactions, and at testing their impact on the correlations between sensory and chemical variables. Seventy-four Italian red whole wines (WWs) from 10 varieties, and corresponding deodorized wines (DWs), were evaluated by sensory descriptive assessment. Total phenols, proanthocyanidins, ethanol, reducing sugars, pH, titratable and volatile acidity were determined. PCA results highlighted different sensory features of the 10 wine types. ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…From a sensory perspective, we recently explored the olfactory-oral cross-modal interactions through sensory and chemical characteristics of a wide set of Italian red wines showing different olfactory and oral features. The results suggested that olfactory cues might play modulation effects on the perceptions of in-mouth sensations, including some astringency sub-qualities, sweet and bitter tastes, supporting the expectations of multimodal sensory interactions between sensations elicited by VOCs and PPhs during red wine tasting [46].…”
Section: Introductionsupporting
confidence: 61%
“…From a sensory perspective, we recently explored the olfactory-oral cross-modal interactions through sensory and chemical characteristics of a wide set of Italian red wines showing different olfactory and oral features. The results suggested that olfactory cues might play modulation effects on the perceptions of in-mouth sensations, including some astringency sub-qualities, sweet and bitter tastes, supporting the expectations of multimodal sensory interactions between sensations elicited by VOCs and PPhs during red wine tasting [46].…”
Section: Introductionsupporting
confidence: 61%
“…However, few studies have focused on the chemical characterisation of wines obtained from these varieties. Recently some comparative studies among the main Italian red wines have been done focusing on the phenolic (Giacosa et al, 2021) and non-volatile metabolomic profile (Arapitsas et al, 2020) as well as on sensory characteristics such as astringency (Pittari et al, 2020;Piombino et al, 2020). However, little is known about their content in monoterpenoids and norisoprenoids, despite the well-documented relevance of these compounds to perceived wine aroma (Black et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our results could somehow explain the “dry,” “harsh” and “dynamic” astringent character, as well as the bitterness of Sagrantino wines [ 36 , 37 ]. The mDP value is only one of the parameters that is able to explain the influence of proanthocyanidins in wine sensorial character.…”
Section: Discussionmentioning
confidence: 92%
“…While the chemical role of the proanthocyanidins is shared by all the red wines, it has emerged that there is a huge diversity in the concentration of these compounds in the grapes from different cultivars [ 20 , 32 , 33 , 34 ]. It is expected that both the differences in the concentration, as well as in the structure, of the tannins can contribute to the huge diversity in the astringency of wines produced from them [ 35 , 36 , 37 ]. The need to build reliable reference values for the composition of each cultivar, to be used in the quality control, and combined with other data, especially the sensory data, calls for the need for accurate measurement via the phloroglucinolysis assay.…”
Section: Introductionmentioning
confidence: 99%